«Մանկութեան Աւետարան»-ի փոխակերպումը Առաքել Բաղիշեցու «Տաղ Աւետման»-ում - Մամյան, Մարի
The Armenian Gospel of the Infancy, like a number of other apocrypha, was used in many literary works such as lives of saints, hymns, and legends. This Gos-pel was also transformed into poetic compositions, among which Hovasap‘ Sebas-tats‘i’s On the Creation and Arakel Baghishets‘i’s Ode to the Annunciation are significant. While in the first poem the author retells in a free manner one of the famed stories of the Gospel of the Infancy (Jesus with the teacher Gamaliel), Ara-kel Baghishets‘i closely follows the apocryphon, describing the Annunciation of Mary in all details. Армянское «Евангелие детства» как и ряд других апокрифов, было включено во многие сборники, такие, как Четьи-Минеи, отразилось в гимнах и сказаниях. Это Евангелие было также переработано в стихотворной форме. Самыми значительными из таких произведений являются поэмы «О бытии» Овасапа Себастаци и «Ода Благовещения» Аракела Багишеци. Однако, в то время как в первой поэме автор в свободной форме пересказывает одну из историй «Евангелия детства» (Иисус у учителя Гамалиила), Аракел Багишеци целиком следует апокрифу, с точностью до малейших деталей описывая Благовещение Марии.
Keywords: Ավետարան; Գրականություն